The Effective Training Management Model of Learning Guardian in BPPLSP Surabaya, Indonesia - Achmad Rasyad (JOURNAL OF EDUCATION, 2013)
This study is aimed at finding  out factors  that determine  the effectiveness  of training processes  factors   that  determine  the  effectiveness  of  training  results.  The study used an ex-post facto  design. A total  of  60 participants  took part  in the study. Datat analysis was done in percentages.   The research finding  shows that factors  such as participants,  trainers, training materials, and working environment play significant roles in the training process; factors  such as participants,  trainers, training materials and  working   environment   affect  the  training   result  with  the finding   notes:   (a) trainees'  do not only significantly  influence  the training  result through  the training process,  but they also have direct  irifluence to the training  result;  (b) the instructors and training materials contribute the training result indirectly; and (c) working environment   does  not  only  significantly   influence  the  training  result  through  the training process,  but it also gives direct irifluence to the training result.